The Scriniodinium crystallinum dinoflagellate cyst zone in the Middle–Upper Oxfordian, Upper Jurassic, Ilimananngip Nunaa (Milne Land), East Greenland - Piasecki, Stefan (Geological Survey of Denmark and Greenland (GEUS), 2024)
The biostratigraphy of the Jurassic in East Greenland is historically based on macroscopic fossils. Stratigraphy based on palynomorphs (spores, pollen and dinoflagellate cysts) has progressed more slowly and sporadically. The Scriniodinium crystallinum dinoflagellate cyst Zone is identified in middle – upper Oxfordian strata of Ilimananngip Nunaa (Milne Land), central East Greenland. The lower boundary is defined by the last occurrence of Trichodinium scarburghense in the Cardioceras tenuiserratum ammonite Zone. The upper boundary is defined by the last occurrence of S. crystallinum in the uppermost Amoeboceras rosenkrantzi ammonite Zone. However, the subzonal division of the S. crystallinum Zone recorded in North-West Europe is not identified in Greenland. Eighteen characteristic dinoflagellate cyst events are considered stratigraphically significant and useful in East Greenland. Fifteen of these events provide an informal, detailed stratigraphical subdivision of the S. crystallinum Zone into 10 subunits. Identification of the zone is an addition to the previously defined upper Bathonian – middle Oxfordian zonation, where the uppermost palynostratigraphical event was recorded to be the last occurrence of T. scarburghense. With this study, the correlation of dinoflagellate cyst and ammonite stratigraphy in the lower and middle Oxfordian is slightly modified. The S. crystallinum Zone documented here, in combination with the zonation used for the stratigraphy of the Blokelv-1, Rødryggen-1 and Brorson Halvø-1 cores of the Upper Jurassic to Lower Cretaceous, completes the dinoflagellate cyst stratigraphy of the marine Jurassic in East Greenland. Together with previous studies of spores and pollen in less marine units, the first complete palynological Jurassic stratigraphy is thus established for the Jurassic succession in East Greenland.